SapWin 4.0–a new simulation program for electrical engineering education using symbolic analysis. Issue 1 (1st July 2015) - Grasso, F.; Luchetta, A.; Manetti, S.; Piccirilli, M. C.; Reatti, A.
ABSTRACT: The paper presents the main capabilities and the possible applications in the teaching area of Electrical/Electronic Engineering of a software system developed by the authors and aimed at simulating analog linear (or linearized) circuits. The work is the enrichment, enhancement and extension of some programs developed by the same authors along the last two decades and distributed in many schools, institutions, industries, and research centers for different purposes. The feedback (in terms of suggestions, corrections, and improvement requests) has been collected to generate a completely renewed software that could definitely become a really efficient tool in the field of analog circuits, also filling the gap which still exists in the use of very famous and classical circuit simulators (as, for instance, the SPICE family). The application of the past experience involves several courses, as it will be described in the final sections of paper. © 2015 Wiley Periodicals, Inc. Comput. Appl. Eng. Educ. 24:44–57, 2016; View this article online atwileyonlinelibrary.com/journal/cae ; DOI10.1002/cae.21671